THE EVALUATION OF EDUCATION IN THE BOOK OF SAḤIḤ AL-BUKHĀRĪ AND SAḤIḤ MUSLIM - Musriaparto Musriaparto; Nawir Yuslim; Syamsu Nahar (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to delve deeper into the evaluation of education, especially Islamic education, contained in the traditions of the Prophet Muhammad SAW which is narrated in two major books, namely the Book of Sahih Bukhori and Sahih Muslim. This research was conducted by classifying the hadiths in the two books into groups of hadith indicated as hadiths about the evaluation of education. As a finding, there are three terms in the two major hadith books, namely Al-Hisab, Al-Bala ', and Al-Imtihan. In the Saheeh Bukhari and Saheeh Muslim books the traditions of the evangelization of education are clearly explained. so that it can be concluded that Islamic Education related to evaluation has been clearly described through the Prophet's hadiths narrated in the books of Sahih Bukhari and Sahih Muslim. Keywords: The Evaluation of Education, Shahih Bukhari, Shahih Muslim